Combined anti-SARS-CoV-2 IgA, IgG, and IgM Detection as a Better Strategy to Prevent Second Infection Spreading Waves. (17th February 2022) - Nuccetelli, Marzia; Pieri, Massimo; Gisone, Francesca; Bernardini, Sergio
ABSTRACT: Coronavirus disease (COVID-19) is challenging many health, economic, and social systems. RT-PCR assays are diagnosis gold standard; however, they can lead to false-negative results. Therefore, anti-SARS-CoV-2 IgG, IgM, and IgA investigation can play a complementary role in assessing the individuals immune status. Majority of serological tests focus on IgM and IgG although IgA are the main immunoglobulins involved in mucosal immunity. It has been reported that digestive symptoms may occur in the absence of any typical respiratory symptom. Thus, a complete screening, comprising IgA, IgM, and IgG detection could be more consistent and useful in patients with atypical symptoms or in paucisymptomatic cases. Current literature describes over 200 immunoassays available worldwide, pointing out a great results variability, depending on methodology or antigens' nature. In our study we evaluated anti-SARS-CoV-2 IgA, IgM, and IgG trend on a control group and on two COVID-19 patient groups (early and late infection time) with a lateral-flow combined immunoassay (LFIA) and an enzyme-linked immunosorbent assay (ELISA). Dissimilar antibodies time kinetics have been described in COVID-19 (decreasing IgM concentration with IgA/IgG persistence for a longer time; as well as persistent IgA, IgG, and IgM concentration); our results confirmed both of them depending on the methodology; therefore, it is difficult to compare different studies outcomes, suggesting the importance of a serological tests international standardization. Nevertheless, we propose a flowchart with combined anti-SARS-CoV-2 IgG/IgM/IgA detection as a screening on general population, where serological positivity should be considered as an "alert, " to avoid and contain possible new outbreaks.